1990
DOI: 10.1177/095646249000100213
|View full text |Cite
|
Sign up to set email alerts
|

Half-Life of Cotton-Wool Spots in the Acquired Immunodeficiency Syndrome

Abstract: Cotton-wool spots are a hallmark of human immunodeficiency virus (HIV) retinopathy in the acquired immunodeficiency syndrome (AIDS). We analysed the half-life of cotton-wool spots in AIDS in a prospective study, and found the average time to disappearance to be 6.9 weeks. HIV retinopathy differs from diabetic retinopathy in having a smaller size cotton-wool spot and a much shorter half-life, suggesting a patchy involvement of the retinal capillaries in AIDS and a widespread capillary disease in preproliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…Features of acute retinal ischemia include venous dilatation and beading, the presence of numerous retinal hemorrhages and cotton wool spots (CWS). CWS in microangiopathic HIV retinopathy tend to be small – our patient’s CWS were large, possibly reflecting a greater degree of retinal ischemia (Mansour et al 1990). …”
Section: Discussionmentioning
confidence: 84%
“…Features of acute retinal ischemia include venous dilatation and beading, the presence of numerous retinal hemorrhages and cotton wool spots (CWS). CWS in microangiopathic HIV retinopathy tend to be small – our patient’s CWS were large, possibly reflecting a greater degree of retinal ischemia (Mansour et al 1990). …”
Section: Discussionmentioning
confidence: 84%
“…The half-life of cotton-wool spots was reported to be 6.9 weeks in HIV-seropositive subjects. 38 Optic nerve pathology (besides cryptococcal infection) was present in 2 patients. Although microglial nodules are frequently identified in the white matter of patients with HIV encephalitis, 39,40 such accumulations of reactive cells in the optic nerve have not been previously reported, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed they were visible anywhere from 4 weeks to 17.2 months depending on underlying disease, patient's age and medication [12,13,18] . Besides these factors, our analysis revealed that the area of CWS as well as the surrounding pathology such as intraretinal cysts, intraretinal hemorrhage and avascular zones seem to be factors associated with the duration of visibility.…”
Section: Discussionmentioning
confidence: 99%